THE INFLUENCE OF CUSTOMER RETENTION STRATEGIES ON THE ORGANIZATION PERFORMANCE OF COMMERCIAL BANKS IN THIKA TOWN - Gitahi, Oliver Kimari; Misango, Sedina (European Journal of Business and Strategic Management, 2020)
Purpose: The concept of customer retention has gained popularity among numerous firms in the goods and services industry. Although extensive research exists on customer retention strategies, limited research is available on the link between customer retention strategies and the organization performance of firms. This study sought to determine the influence of customer retention strategies on the organization performance of commercial banks in Thika Town of Kiambu County. Methodology: The study adopted descriptive research design. The population of interest for the study was the employees of the 22 commercial banks in Thika, which made a target population of 227. This study used purposive sampling where the branch managers, operations manager, credit managers, relationship officers and customer experience consultants of the commercial banks in Thika town, who are 121 in number, were included. The semi-structured questionnaire that comprised of closed-ended questions and open-ended questions were used as data collection instruments. Data was analysed using the Statistical Package for Social Sciences version 21. Regression analysis and correlation was used to determine the relationship and direction of variables respectively. Findings: The findings were presented based on the specific objectives in the form of frequencies, tables, and charts. The study revealed that banks used various service distribution channels including Internet banking, Agency banking, Automatic Teller Machines and Mobile banking and POS Terminals. The study concluded that provision of quality service, employment of loyalty and rewards programs and a strong corporate image had a direct positive influence on the performance of Commercial Banks in Thika town. Unique contribution to theory, practice, and policy: Banks should therefore ensure continuous innovation in distribution and invest in strategies that promote quality services. In addition, banks should invest in loyalty and rewards programs and invest in the enhancement of their corporate image in order to continue improving their performance.